Python scripts for web scraping metadata from descriptions of the international scenario of research data repositories - Alexandre Ribas Semeler; Arthur Longoni Oliveira; Fabiana Andrade Pereira; Policarpo Matiquite (Encontros Bibli)
Objective: Research data repositories are an evolution of document repositories that aim to access and preserve all materials used before, during, and after scientific research. In this context, this study aims to conduct an exploratory and descriptive investigation of the international scenario of data repositories by monitoring the descriptive metadata of the international register of this type of repositories in the Registry of Research Data Repositories (re3data.org).